IMPLEMENTASI METODE MEMBACA NYARING DAN MENDENGAR MUROTTAL AL- QUR`AN DALAM MENINGKATKAN HAFALAN SANTRI DI PONDOK PESANTREN NURUL AHMADI CATAK GAYAM MOJOWARNO JOMBANG - Nur Rofikul Maulidah (PAI FAI UNHASY Tebuireng Jombang, 2023)
This article intends to discuss the implementation of the method of reading aloud and listening to the murottal Qur'an in increasing the memorization of students at Pondok Pesantren Nurul Ahmadi Catak Gayam Mojowarno Jombang. This research uses a qualitative method that aims to find out something in depth. This research is included in the case study by analyzing what was stated by Miles and Huberman. The data obtained are the results of observations, interviews and documentation which are then analyzed and concluded. The results of the study found that the planning method for reading aloud and listening to murattal al-Qur'an was when the teacher wanted to memorize the students' readings by the teacher and then students imitated so that they could be more thorough in reading, reading and makhoijul letters. supporting factors are mentoring, availability of tools, integration between institutions and pesantren, time management and a good system. While the inhibiting factor is the lack of students who have difficulty in applying recitation and makharijul letters when reading the Qur'an, the feeling of laziness and boredom felt by students.